Influence of STAD cooperative learning model to improving physics learning process and learning outcomes - M. Yusuf As (Jurnal Pijar Mipa, 2021)
Efforts to improve student learning processes and outcomes use the STAD type cooperative learning model with the following stages: (1) teaching, presenting lessons; (2) discussion, students work in their groups guided by activity sheets to complete the subject matter; (3) test, students take the quiz individually; and (4) group rewards. The data collected in this study were in the form of activity observation data, questionnaires, and learning outcomes tests. The results showed that the students' activities were in the very active category in cycle 1, very active in cycle 2, and the very active category in cycle 3. The teacher's activities were in the very active category in the three cycles. The average cognitive aspect of students is 76 with classical completeness 74% in cycle 1, the average cognitive aspect of students is 75 with classical completeness 83% in cycle 2, and the average value of cognitive aspect is 82 with classical completeness 91 % in cycle 3. The results of the ANOVA analysis in the treatment of each cycle showed a significant effect with a value of 0.01 below 0.05. Based on this data, it can be concluded that the application of the STAD type cooperative learning model can improve the process and learning outcomes of class X in the Physics lesson of SMKN 1 Narmada.